2019
DOI: 10.3897/compcytogen.v13i3.36449
|View full text |Cite
|
Sign up to set email alerts
|

Banded karyotype of Nelore cattle (Bos taurus indicus Linnaeus, 1758)

Abstract: Chromosome banding techniques were applied and standardized to obtain karyotype characteristics for the first time in Brazil of Nelore cattle – Bos taurus indicus Linnaeus, 1758 – (bovine subspecies most prominent in Brazilian livestock). Blood samples were collected from the animals of the School of Agrarian and Biological Sciences of the Pontifical Catholic University of Goiás, two males and two females of pure breed. These samples were submitted to the cell culture method to study metaphase chromosomes. Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…2). This is like the standard CBG-banding pattern of cattle as reported for Red Danish (Hansen 1973), Bos taurus L. (Iannuzzi and Berardino 1985), Jersey crossbreds (Chauhan et al 2009), Tho-Tho cattle (Longkumer et al 2015), mithun (Ezung 2016) and Nellore cattle (Amancio et al 2019). However, the unpaired acrocentric chromosome with a small p-arm also stained darkly throughout the length showing no centromere banding (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…2). This is like the standard CBG-banding pattern of cattle as reported for Red Danish (Hansen 1973), Bos taurus L. (Iannuzzi and Berardino 1985), Jersey crossbreds (Chauhan et al 2009), Tho-Tho cattle (Longkumer et al 2015), mithun (Ezung 2016) and Nellore cattle (Amancio et al 2019). However, the unpaired acrocentric chromosome with a small p-arm also stained darkly throughout the length showing no centromere banding (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Red Kandhari (Katkade 2005), Khillari (Nakod 2013), Malnad Gidda (Suresh et al 2015), Indonesian native bulls (Ciptadi et al 2017) and Nellore cattle (Amancio et al 2019). The GTG-banding results also confirmed that there was no translocation between autosomes and Y-chromosome, as all the autosomes were having the typical G-banding pattern, as those of Iannuzzi and Di Meo (1995) and ISCNDB 2000 (Cribiu et al 2001).…”
Section: Resultsmentioning
confidence: 81%
“…In our opinion, a relatively high frequency of centric fusions of chromosomes in agricultural animals may be determined on the cellular level by nucleolus organizers since the chromosome sites, used in the processes of centric fusion, are concentrated in these very sites. DISCUSSION Much information has been accumulated within 40 recent years regarding the comparative analysis of dif-ferentiated banded chromosomes of different species of animals which allowed to determine the main tendencies in the karyotype evolution within many taxa (Robinson TJ et al, 2011;Amancio AP et al, 2019). The chromosomal evolution is understood as the processes related to transformations (reformatting) of mutually located sites of genome, which, on the cytological level, results in a change in the number of chromosomes and chromosomal transformations and in a change in the amount of euchromatin in the chromosomes as well as the modifi cation of the number and localization of nucleolus organizers (Ruiz-Herrera A et al, 2006;Qumsiyeh MB, 1999).…”
Section: Results Of Studiesmentioning
confidence: 99%
“…The karyotypes of genus Alburnus (Rafinesque, 1820) are symmetric in two species, and between symmetric and asymmetric in five species (Eroğlu, 2016). Pelophylax ridibundus (Pallas, 1771) and Bos taurus indicus (Linnaeus, 1758) have symmetric, and between symmetric and asymmetric karyotypes, respectively (Canpolat et al, 2018;Amancio et al, 2019).…”
Section: Resultsmentioning
confidence: 99%